Acute renal failure unmasking Lesch-Nyhan disease in a patient with tuberous sclerosis complex. (July 2016) - Thumfart, Julia; Weschke, Bernhard; Ringe, Hannelore; Weinhold, Natalie; Müller, Dominik
Abstract: Case report: We report on a male patient with Tuberous Sclerosis Complex (TSC), which was prenatally diagnosed. At the age of 3 months the patient developed acute renal failure with excessive hyperuricemia. Kidney function improved after rehydration and application of rasburicase, however without full recovery. Due to the inappropriate high levels of uric acid compared to kidney function, screening of hypoxanthine-guanine phosphoribosyltransferase (HPRT) related diseases was initiated. Mutation analysis revealed a deletion of exon 2 and 3 of the HPRT gene confirming the diagnosis of Lesch-Nyhan Disease (LND). After initiation of allopurinol therapy renal function further improved. In the following months the patient developed clinically a typical neurological phenotype of LND and TSC with seizures, severe dystonia and developmental delay. Conclusion: Acute renal failure is a rare complication of HPRT related diseases. Combination of two inherited diseases may lead to a delayed diagnosis due to a mixed and maybe misleading phenotype. Highlights: This case reports a mixed phenotype due to two different diseases. Combination of two inherited diseases may lead to a delayed diagnosis. Acute renal failure is a rare complication of Lesch-Nyhan disease.